Reduction of Pain Thresholds in Fibromyalgia after Very Low-Intensity Magnetic Stimulation: A Double-Blinded, Randomized Placebo-Controlled Clinical Trial - Ceferino Maestú; Manuel Blanco; Angel Nevado; Julia Romero; Patricia Rodríguez-Rubio; Javier Galindo; Juan Bautista Lorite; Francisco de las Morenas; Pedro Fernández-Argüelles (Pain Research and Management)
BACKGROUND: Exposure to electromagnetic fields has been reported to have analgesic and antinociceptive effects in several organisms.